Defective ADAMTS13 synthesis as a possible consequence of NASH in an obese patient with recurrent thrombotic thrombocytopenic purpura. (20th February 2014) - Lombardi, Anna Maria; Fabris, Roberto; Berti de Marinis, Giulia; Marson, Piero; Navaglia, Filippo; Plebani, Mario; Vettor, Roberto; Fabris, Fabrizio
Abstract Objectives Thrombotic thrombocytopenic purpura (TTP) is a rare and devastating hematologic disorder frequently associated with multiple organ failure and sometimes death. This syndrome is mainly associated with severe deficiency of ADAMTS13, a disintegrin and metalloprotease with thrombospondin (TSP)‐1 repeats, cleaving high molecular weight von Willebrand Factor (ULVWF) multimers. Decreased plasma ADAMTS13 activity results in the accumulation of ULVWF multimers with consequent platelet activation. Recently, obesity has been considered as a potential independent risk factor for TTP, but the reason of this association is still unknown. Methods and results We describe an unusual case of fatal recurrent TTP in a morbid obese female with non‐alcoholic steatohepatitis (NASH) and severe ADAMTS13 activity deficiency due neither to an inhibitory autoantibody nor to a gene mutation. Conclusions Visceral obesity is associated with non‐alcoholic fatty liver disease (NAFLD) and NASH: we hypothesized that these conditions can influence ADAMTS13 antigen and activity. In fact, hepatic stellate cells (HSC) are the main producers of ADAMTS13, and a decrease in ADAMTS13 activity has been reported in liver disease.